Models of Water Erosion and Soil Loss Tolerance in Dystrophic Oxisols in Southern Minas Gerais - Tavares, André Silva; Mendes Júnior, Henrique; Spalevic, Velibor; Mincato, Ronaldo Luiz (Universidade de São Paulo. Faculdade de Filosofia, Letras e Ciências Humanas, 2017)
Different methods of calculating soil losses by water erosion were compared with Soil Loss Tolerance in tropical Oxisols. The Potential Erosion Method and the Revised Universal Soil Loss Equation were used. The Potential Erosion Method was calculated by the Erosion and Flow Intensity software and an average soil loss of 1.46 Mg ha-1 year -1 with a maximum discharge of 649.31 Mg year-1 was obtained. Alternatively, an average soil loss of 1.52 Mg ha-1 year-1 with a maximum discharge of 668.26 Mg year-1 was obtained by the Universal Equation of Revised Soil Loss. Soil losses calculated by the two methods were similar and fell below the Soil Loss Tolerance limit, which ranged from 5.19 to 5.90 Mg ha-1 year-1 and validate the application of the Potential Erosion Method in Tropical soils of southern Minas Gerais State.